A genome-wide study of lipid response to fenofibrate in Caucasians: a combined analysis of the GOLDN and ACCORD studies. Issue 7 (July 2016) - Irvin, Marguerite R.; Rotroff, Daniel M.; Aslibekyan, Stella; Zhi, Degui; Hidalgo, Bertha; Motsinger-Reif, Alison; Marvel, Skylar; Srinivasasainagendra, Vinodh; Claas, Steven A.; Buse, John B.; Straka, Robert J.; Ordovas, Jose M.; et al.
Abstract : Background: Fibrates are commonly prescribed for hypertriglyceridemia, but they also lower LDL cholesterol and increase HDL cholesterol. Large interindividual variations in lipid response suggest that some patients may benefit more than others and genetic studies could help identify such patients. Methods: We carried out the first genome-wide association study of lipid response to fenofibrate using data from two well-characterized clinical trials: the Genetics of Lipid Lowering Drugs and Diet Network (GOLDN) Study and the Action to Control Cardiovascular Risk in Diabetes (ACCORD) Study. Genome-wide association study data from both studies were imputed to the 1000 Genomes CEU reference panel (phase 1). Lipid response was modeled as the log ratio of the post-treatment lipid level to the pretreatment level. Linear mixed models (GOLDN, N =813 from 173 families) and linear regression models (ACCORD, N =781) adjusted for pretreatment lipid level, demographic variables, clinical covariates, and ancestry were used to evaluate the association of genetic markers with lipid response. Among Caucasians, the results were combined using inverse-variance weighted fixed-effects meta-analyses. The main findings from the meta-analyses were examined in other ethnic groups from the HyperTG study ( N =267 Hispanics) and ACCORD ( N =83 Hispanics, 138 African Americans). Results: A known lipid locus harboring the pre-B-cell leukemia homeobox 4 ( PBX4 ) gene on chromosome 19 is important for LDL cholesterol response to fenofibrate (smallest P =1.5×10 −8 ). The main results replicated with nominal statistical significance in Hispanics from ACCORD ( P <0.05). Conclusion: Future research should evaluate the usefulness of this locus to refine clinical strategies for lipid-lowering treatments. Abstract : Supplemental Digital Content is available in the text.